2002
DOI: 10.1046/j.1365-2052.2002.00811.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association of GH1 and POU1F1 gene variants with meat production traits in Piemontese cattle

Abstract: Growth hormone (GH) and the Pit-1 transcription factor have been shown to be involved in the physiological mechanisms related to growth. The present study was carried out to investigate the possible association of the polymorphism at GH1 and POU1F1 loci with meat production traits in Piemontese cattle. Fourteen traits were considered, expressing growth (weight at 5, 7 and 11 months, daily gain), size [withers height (WH), trunk length (TL), chest girth (CG) at 12 months] and meat conformation [withers width (W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 14 publications
5
22
0
Order By: Relevance
“…Our results for the POU1F1/Hinf I polymorphism showed no significant effect of the on growth or carcass traits, indicating that this is not a molecular marker associated with meat production in beef cattle and supporting the work of other published studies (Zwierzchowski et al, 2001;Di Stasio et al, 2002;Zhao et al, 2004). However, Renaville et al (1997) reported that in taurine Belgian Blue cattle, POU1F1/Hinf I BB animals were significantly superior to animals with the AB and AA genotypes in terms of body weight at 7 months of age and Carrijo et al (2003) found that for the mixed race taurine/zebu Canchim breed the BB genotype was superior to the AB and AA genotypes for weaning and yearling weight.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Our results for the POU1F1/Hinf I polymorphism showed no significant effect of the on growth or carcass traits, indicating that this is not a molecular marker associated with meat production in beef cattle and supporting the work of other published studies (Zwierzchowski et al, 2001;Di Stasio et al, 2002;Zhao et al, 2004). However, Renaville et al (1997) reported that in taurine Belgian Blue cattle, POU1F1/Hinf I BB animals were significantly superior to animals with the AB and AA genotypes in terms of body weight at 7 months of age and Carrijo et al (2003) found that for the mixed race taurine/zebu Canchim breed the BB genotype was superior to the AB and AA genotypes for weaning and yearling weight.…”
Section: Discussionsupporting
confidence: 78%
“…Regitano et al (1999) observed a significant linear increase in the V allele over four generations in a Canchim herd and suggested that this polymorphism may be associated with phenotypic traits that are subject to selection in this herd. Sartore and Di Stasio (2000) also suggested the occurrence of indirect selection for the V allele in Piedmontese cattle, although in a subsequent study (Di Stasio et al, 2002) these authors found no evidence of an association between this polymorphism and growth or carcass traits in this breed. Tambasco et al (2003) observed that LL genotype Canchim x Nellore, Simmental x Nellore and Angus x Nellore crossbred cattle presented higher weight gain from birth to weaning as compared to the LV genotype, although from weaning to yearling the opposite was true.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Therefore, the GH gene is a promising candidate gene worth studying for its effects on milk performance, growthrelated traits and reproduction traits (Di Stasio et al, 2002;Franco et al, 2005). *For correspondence: Tel: +86-029-87091379; Fax: +86-029-87092164; E-mail: chenhong1212@263.net …”
Section: Introductionmentioning
confidence: 99%
“…POU1F1 has been studied as a candidate gene for genetic variation in meat production traits, because of the essential role of its products in the physiological mechanisms related to growth [33][34][35]. Moreover, POU1F1 has been considered to be a potential major gene or marker for growth traits, because it is significantly associated with body weight and average daily weight gain [36]. The results of our association study on the SUCLG2 polymorphism are consistent with our hypothesis that the significant SNP in SUCLG2 may play important roles in growth via regulation of the expression of POU1F1.…”
Section: Analysis Of Transcription Factor Binding Sites Of Significanmentioning
confidence: 99%